2015
DOI: 10.17795/nmsjournal27714
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Objective Structured Assessment of Technical Skills (OSATS) and Traditional Method on Learning of Students

Abstract: Background:Despite the benefits of the objective structured assessment of technical skills (OSATS) and it appropriateness for evaluating clinical abilities of nursing students , few studies are available on the application of this method in nursing education.Objectives:The purpose of this study was to compare the effect of using OSATS and traditional methods on the students’ learning. We also aimed to signify students’ views about these two methods and their views about the scores they received in these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…[16] Results of another study indicated better effect of objective structured assessment of technical skills on learning. [17]…”
Section: Discussionmentioning
confidence: 99%
“…[16] Results of another study indicated better effect of objective structured assessment of technical skills on learning. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Objective structured assessment of technical skills (OSATS) has been implemented to measure MD surgeons' performances for surgical skill assessment . Construct validity of OSATS has been demonstrated using benchtop models, simulation motion metrics, animal models, and operating room performance among MD surgeons . A previous study has investigated and in part validated a modified OSATS system for veterinary surgeons, which demonstrated similar result as in MD surgeons …”
Section: Introductionmentioning
confidence: 99%
“…13,[31][32][33][34] Construct validity of OSATS has been demonstrated using benchtop models, simulation motion metrics, animal models, and operating room performance among MD surgeons. 33,[35][36][37][38] A previous study has investigated and in part validated a modified OSATS system for veterinary surgeons, 26 which demonstrated similar result as in MD surgeons. 7,32,33,[35][36][37] Simulation training preferably starts early in the career of the MIS surgeon, ideally before or simultaneously with the first exposure to MIS in the operating room.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of nursing care must prepare students to carry out and accept professional responsibility in a changing clinical environment [3][4][5]. Only in a clinical environment does a nurse's knowledge become most evident [6]. Because of the importance of clinical training, appropriate strategies for clinical assessment must be sought, with the purpose of specifying a success rate of clinical training [7].…”
Section: Introductionmentioning
confidence: 99%